Potencialidade das assinaturas isotópicas de Pb por espectrometria de massa ICP-MS e TIMS no estudo da proveniência dos azulejos das fachadas históricas de Belém, PA - OLIVEIRA, Etiana Costa (Universidade Federal do Pará, 2019)
Since the eighteenth century, frontages of old buildings from the city of Belem and others Brazilian cities like Salvador, Recife, Rio de Janeiro and São Luis, have been covered with tiles imported principally from Portugal and from others countries of Western Europe, constituting and valorous historical patrimony. The purpose of this study is to evaluate the potentiality of Pb isotopes as a tool for the identification of the provenience of the tiles of historical building from Belem by lead isotope analyses of the tile’s glaze compared with possible Pb ores deposits sources in Western Europe. The study included a comparison of Pb isotopic results obtained by Thermo-ionization mass spectrometry (TIMS) and ICP- mass spectrometry (ICP-MS) on a Finnigan MAT 262 mass spectrometer and a Thermo-Finnigan Neptune ICP-MS mass spectrometer, respectively. Pb isotopes were determined on 36 samples of tiles (23 tiles from Portugal, 5 tiles from England, 4 tiles from France, 4 from Germany). Six samples of tile from the city of São Luis an of unknowm origin , including from de seventeen century, 4 from the eighteenth century and from nineteenth century were also investigated. Additionaly, Pb isotope analyses were also performed on 8 samples of Brazilian modern tiles to evaluate possible distinction between isotopic signature of original European tiles and national replications. A compilation of isotopic signatures of the main Pb deposits in Western Europe and Brazil was necessary in order to compare the Pb isotope compositions of the deposits and tiles. According to the chemical composition and, principally, the high Pb contents of the glaze a simple analytical procedure by HF leaching was adopted for Pb extraction of the glaze, without chemical separation and purification by ion-exchange chromatography. The measurements of Pb isotopic composition by TIMS and ICP-MS on the same samples displayed some differences but these differences do not affect the interpretations of the results. The 208Pb/206Pb vs. 207Pb/206Pb diagram is shown to be the most helpful for the discussion of the Pb isotopic signatures. When comparing with the field of isotopic signatures of Western Europe deposits as probable source of the Pb of the glazes, isotopic compositions indicate that no direct relationship can be established between the country of fabrication of the tile and the country of production of the Pb. Almost the countries from Western Europe may have furnished glaze’s lead. However, Spain (Alcudia Valley), England / Whales and, probably, France have been the main furnishers. Lead produced by the Portuguese deposits and the Cartagena deposits in Spain were not used for the fabrication of the historical study tiles. The similarities in age and geological context of the Pb ore deposits from Western Europe provoked an overlap between the Pb isotopes fields from several countries, making difficult to distinguish the Pb provenience, principally for England, France, Germany and Belgium. Others factors like overlapping of the Pb isotopic signatures produced by different countries, evidences of Pb mixing from several deposits used for the tile fabrication and the lack of confident historical informations about Pb mining and trading in Western Europe, also limited the use of Pb isotopic composition from the tile provenience. Despite these limitations, this study permitted to identify a specific and homogeneous Pb isotopic signature for the older tiles, made before the nineteenth century. It has been also possible to point out the utilization of Pb imported from other continents for the fabrication of some Portuguese, English and German tiles at the end of 19th century or the beginning of the 20th century which is in good agreement with the declining of Pb mining in western Europe during the second half of the 19th century. Portuguese tiles displayed a roughly homogeneous Pb isotope signature depending on the furnisher as well as distinct Pb signatures from furnisher to another one. Then a refining of the study on the base of a larger set of European tiles would possibly be able to be used as a helpful tool for determination of the age and maker of the tiles covering the frontage of historical buildings in Brazil. Finally, this study indicated that Pb used for the fabrication of modern Brazilian tiles and replications of historical tiles of the city of São Luis came from a mixture of Pb from the State of Bahia (Boquira and Nova Redenção deposits). The overlapping of some of the Brazilian modern samples with the field of Western Europe lead deposits and with some of the historical tiles from Western Europe restrain the capability for Pb isotope signature to be employed for distinction between modern and historical tiles.